Pengaruh Kepemilikan Keluarga Terhadap Kinerja Keuangan Perusahaan: Efek Moderasi dari Keterlibatan Keluarga - Melati Oktafiyani; Jesica Viranco Intan Miranda; Nila Tristiarini; St. Dwiarso Utomo (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
This study aims to analyze the moderating role of family involvement on the effect between family ownership on financial performance while taking into consideration the characteristic of the company (size). Using time series dataset, this study covers a sample of 32 public companies (288 company-years) listed on the Indonesian Stock Exchange (IDX) over the period 2010-2018. The family business category is defined as FPEC-Scale (Power Dimensions). The finding shows that family ownership positively affects the financial performance. In addition, the other findings indicate that the more the family is involved in the management and corporate governance, the more financial performance appears to be sustained over the long term. On the other hand, the relationship of family ownership and financial performance is moderated by family involvement. It emphasizes the importance of holding CEO positions in the family business by family members, in particular founders, in order to achieve better financial performance.